O efeito de uma intervenção educativa para o ensino de enfermeiros sobre terapia nutricional enteral - Carrasco, Viviane, 1979- (2019)
Orientadores: Ana Railka de Souza Oliveira Kumakura, Maria Isabel Pedreira de Freitas